Strengthening of Student Character Education Through Local Values of Nggusu Waru in Social Studies Learning in Schools - Nurlaili Nurlaili; Muhammad Yamin (Journal of Social Studies Education, 2025)
The rapid development of the postmodern era in the world of education and science and technology has had a significant impact on the character education of students in social life. The progress of the postmodern era can have both positive and negative impacts on the Indonesian nation. For this reason, action is needed to strengthen cultural and religious filtering. Through strengthening character education in social studies learning in schools. This is intended so that the impact and influence of globalization on technological development can be minimized and not damage the existence of cultural values and morality of the nation's generation. This study aims to find out the concept of strengthening education through the values of Nggusu Waru in social studies learning and then analyze the level of strengthening students' character education in schools. The research method used is a qualitative approach with a literature study design. The results of this study show that efforts to strengthen the character education of students and generations require the collaboration of parents as guardians of students, teachers, and stakeholders in various elements of educational institutions. So that it can improve student achievement and young people's life insights about the importance of ethics and morals in the school environment and the wider community.